2021
DOI: 10.5217/ir.2019.09159
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of vedolizumab in ulcerative colitis in patients from Asian countries in the GEMINI 1 study

Abstract: Background/Aims: The efficacy and safety of vedolizumab in moderate to severely active ulcerative colitis (UC) have been demonstrated in the GEMINI 1 study (NCT00783718). This post-hoc exploratory analysis sought to establish the efficacy and safety of vedolizumab in a subgroup of patients from Asian countries with UC from GEMINI 1.Methods: Efficacy outcomes of interest were clinical response, clinical remission and mucosal healing at week 6 (induction phase); and clinical remission, durable clinical response,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…[20] The concomitant use of tofacitinib and immunomodulators is contraindicated; therefore, only patients who received vedolizumab showed concomitant use of immunomodulators in the baseline analysis of UC patients. [21] Likewise, for patients with CD, most of the baseline characteristics were similar between the two drug groups, with a few exceptions. The CDAI score, for instance, was higher in the ustekinumab group than in the vedolizumab group.…”
Section: Discussionmentioning
confidence: 93%
“…[20] The concomitant use of tofacitinib and immunomodulators is contraindicated; therefore, only patients who received vedolizumab showed concomitant use of immunomodulators in the baseline analysis of UC patients. [21] Likewise, for patients with CD, most of the baseline characteristics were similar between the two drug groups, with a few exceptions. The CDAI score, for instance, was higher in the ustekinumab group than in the vedolizumab group.…”
Section: Discussionmentioning
confidence: 93%
“…Similarly, in moderate–to-severe CD Japanese patients, vedolizumab was not found to be better than placebo at both 10 weeks (CDAI-100 response) and 60 weeks (clinical remission) [103]. However, data from post hoc analysis of UC patients in the GEMINI 1 trial from Asian countries have shown efficacy and safety of vedolizumab to be broadly consistent with that of overall study population [104]. Moreover, pharmacokinetic profile of vedolizumab was found to be similar between Asians and non-Asian moderate-to-severe UC and CD, thus supporting the use of vedolizumab flat-fixed dosing in Asian patients as well [105].…”
Section: Evolving Paradigmsmentioning
confidence: 99%
“…1 Introduction of biologics has offered a hope that with improved disease control rates of surgical interventions for disease management will be reduced. [2][3][4] However, after an initial decrease, [5][6][7][8] rates of sur-tion is specific to the gut, however, concerns remain about overall effects on perioperative surgical complications. [11][12][13] Initial report by Lightner et al 9 indicated increase in rates of perioperative infectious complications.…”
Section: Introductionmentioning
confidence: 99%
“…
gery have plateaued for both ulcerative colitis (UC) and Crohn' s disease (CD) while significant concerns have been raised about increasing rates of peri-operative complications. [2][3][4] Anti-tumor necrosis factor (anti-TNF) medications, in particular infliximab, have been shown to increase rates or perioperative infectious complications although this data remains controversial. 3,[8][9][10] It has also been suggested that concerns about anti-TNF related surgical complications is at least in part responsible for the increased rate of 3 stage surgery for UC in the United States.
…”
mentioning
confidence: 99%